Functional filler and thermoplastic resin composite material containing same
By preparing the functional filler BN@PGMA@NH2-In2O3, the problem of insufficient mechanical properties and thermal conductivity of thermoplastic resins is solved, and the performance is significantly improved and the application field is expanded.
Patent Information
- Application Number
- CN202311269951.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
In some application fields, existing thermoplastic resins have insufficient mechanical properties and thermal conductivity, making it difficult to meet the high-demand application needs.
By preparing a functional filler BN@PGMA@NH2-In2O3, the mechanical and thermal conductivity of thermoplastic resins are improved by utilizing the high thermal conductivity of BN, the heterophase nucleation of In2O3 and the surface coating effect of PGMA.
It significantly improves the mechanical properties and thermal conductivity of thermoplastic resins, expanding its application areas.
Smart Images

Figure BDA0004475280680000051 
Figure BDA0004475280680000061 
Figure BDA0004475280680000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer fillers, and specifically relates to a method for preparing a functional filler, and also relates to a thermoplastic resin composite material. The thermoplastic resin composite material contains the functional filler, and the functional filler is prepared by the preparation method herein. Background Art
[0002] Thermoplastic resin is a widely used polymer polyester resin. It has the properties of softening when heated and hardening when cooled, and it does not react chemically. No matter how many times the heating and cooling are repeated, this property can be maintained. This type of resin is a high molecular weight solid at room temperature. It is a linear or slightly branched polymer. There is no cross-linking between molecules. They only attract each other with the help of van der Waals force or hydrogen bonds. During the molding process, the resin softens and flows when it is pressurized and heated. No chemical cross-linking occurs. It can be shaped in the mold and cooled to obtain the desired shape of the product. During repeated heating, the molecular structure basically does not change. When the temperature is too high or the time is too long, it will degrade or decompose. These are the characteristics that distinguish it from thermosetting resins.
[0003] At present, in some specific application fields, the requirements for the mechanical properties and thermal conductivity of thermoplastic resins are relatively high. Most of them are endowed with corresponding mechanical properties and thermal conductivity by adding some functional fillers. The development of new functional fillers is also known as a research hotspot in the current polymer field.
[0004] The present invention is dedicated to explaining a method for preparing a functional filler. The functional filler obtained by the preparation method can improve the mechanical properties and thermal conductivity of the thermoplastic resin when added to the thermoplastic resin system, which has very important practical significance for expanding the application field of thermoplastic resins. Summary of the invention
[0005] In view of this, it is necessary for the present invention to provide a method for preparing a functional filler. The functional filler prepared by the preparation method can improve the mechanical properties and thermal conductivity of thermoplastic resins. As a new type of functional filler, it can expand the application field of thermoplastic resins.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention first provides a method for preparing a functional filler, comprising the following steps:
[0008] Get In2O3;
[0009] Take the In2O3, hydrogen peroxide and deionized water, react at room temperature for 8-12 hours to obtain OH-In2O3;
[0010] The OH-In2O3, γ-aminopropylmethyldiethoxysilane and deionized water are mixed and reacted at 30-50° C. for 8-12 hours to obtain NH2-In2O3;
[0011] Glycidyl methacrylate, initiator, surfactant, deionized water and boron nitride were reacted at 40-60°C for 8-12h to obtain BN@PGMA;
[0012] The NH2-In2O3, BN@PGMA, anhydrous ethanol and deionized water are mixed and reacted at 60-70°C for 5-7h to obtain a functional filler with a composition of BN@PGMA@NH2-In2O3.
[0013] In a further embodiment, the preparation of In2O3 comprises the following steps:
[0014] Take ammonia water, indium nitrate and deionized water, react at 60-80°C for 10-12h to obtain solid A;
[0015] The solid A is calcined at 670-710° C. for 8-12 hours to obtain In2O3.
[0016] In a further embodiment, in the step of obtaining solid A, the mass ratio of ammonia water, indium nitrate and deionized water is (40-50):(36-40):(100-120).
[0017] In a further embodiment, in the step of obtaining OH-In2O3, the mass ratio of In2O3, hydrogen peroxide and deionized water is (30-40): (40-48): (80-100).
[0018] In a further embodiment, in the step of obtaining NH2-In2O3, the mass ratio of OH-In2O3, γ-aminopropylmethyldiethoxysilane and deionized water is (30-40): (28-32): (80-100).
[0019] In a further embodiment, in the step of obtaining BN@PGMA, the mass ratio of glycidyl methacrylate, initiator, surfactant, deionized water, and boron nitride is (30-40): (0.2-0.4): (0.3-0.5): (80-100): (36-42).
[0020] In a further embodiment, the initiator and surfactant used in this article can be conventionally selected in the art. In some specific embodiments of the present invention, the initiator is ammonium persulfate; the surfactant is sodium lauryl sulfate.
[0021] In a further embodiment, in the step of preparing BN@PGMA@NH2-In2O3 functional filler, the mass ratio of NH2-In2O3, BN@PGMA, anhydrous ethanol and deionized water is (30-40): (36-42): (40-50): (80-120).
[0022] The present invention further provides a thermoplastic resin composite material, which is prepared by weight of 85-115 parts of thermoplastic resin, 8-16 parts of functional filler and 0.1-0.5 parts of antioxidant, wherein the functional filler is prepared by the above-mentioned preparation method;
[0023] Further, the antioxidant is not particularly limited, and specific examples include but are not limited to at least one of antioxidant 168, antioxidant 1010, and antioxidant 1330;
[0024] Furthermore, the functional filler prepared by the preparation method in this article is suitable for conventional thermoplastic resins in the art, and specific examples that can be mentioned include one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
[0025] The present invention further provides a method for preparing the thermoplastic resin composite material as described above, comprising the following steps:
[0026] Weigh 85-115 parts of thermoplastic resin, 8-16 parts of functional filler and 0.1-0.5 parts of antioxidant according to weight ratio, mix and stir evenly to obtain a mixture;
[0027] The mixed material is extruded and granulated to obtain a thermoplastic resin composite material.
[0028] Beneficial effects of the present invention:
[0029] The present invention first prepares a functional filler, and its preparation principle is: BN@PGMA with poly(glycidyl methacrylate) coated on the surface is prepared and NH2-In2O3 is obtained by modifying In2O3 with γ-aminopropylmethyldiethoxysilane, and finally BN@PGMA and NH2-In2O3 are bonded together by chemical bonds to obtain a functional filler of BN@PGMA@NH2-In2O3 type.
[0030] In this functional filler: ① BN itself has high thermal conductivity, and its addition improves the thermal conductivity of thermoplastic resin. ② In2O3 can be used as a heterogeneous nucleating agent to promote and improve the crystallization performance of thermoplastic resin and improve the mechanical properties of thermoplastic resin. ③ PGMA coating the surface of BN can improve the compatibility between BN and thermoplastic resin, increase the interfacial interaction between the two, and promote the mechanical properties of thermoplastic resin.
[0031] The effect of the functional filler is better than that of adding separate fillers separately, and has more practical application prospects. DETAILED DESCRIPTION
[0032] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In addition, unless otherwise specified, methods that do not specifically record conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.
[0034] The raw material information used in the following examples and comparative examples is as follows:
[0035] PBT (model 2002U), Polyplastics of Japan; PP (model Z30S), Maoming Petrochemical; PE (model 5070), Panjin Ethylene; PA6 (model CM1017), Toray of Japan; PET (model 008L), Aclo of Canada.
[0036] Glycidyl methacrylate, Jinan Mingwei Chemical Co., Ltd.; sodium lauryl sulfate, Shandong Xintannuo Chemical Co., Ltd.; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; ammonium persulfate, Shandong Chuangying Chemical Co., Ltd.; boron nitride, Guangzhou Hongwu Material Technology Co., Ltd.; ammonia water, Jinan Mengqiao Chemical Co., Ltd.; indium nitrate, Hubei Chengfeng Chemical Co., Ltd.; hydrogen peroxide, Hefei Yingheng Chemical Co., Ltd.; γ-aminopropylmethyldiethoxysilane, Hangzhou Jessica Chemical Co., Ltd.; anhydrous ethanol, Shandong Taixi Chemical Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF.
[0037] The test methods and test conditions used to obtain the composite materials in the following examples and comparative examples are as follows:
[0038] Tensile strength: ASTM D638, the tensile specimen used is (170.0±5.0)mm×(10.0±0.5)mm×(4.0±0.2)mm, and the tensile rate is 5mm / min;
[0039] Flexural modulus: ASTM D790, the bending specimen used is (80.0±5.0)mm×(10.0±0.5)mm×(4.0±0.2)mm, and the bending rate is 2mm / min;
[0040] Izod impact strength: ASTM D256, the notched Izod impact strength specimen used is (80.0±5.0)mm×(10.0±0.5)mm×(4.0±0.2)mm, the notch is machined, and the notch depth is (2.0±0.2)mm;
[0041] Thermal conductivity: ASTM D5470, the thermal conductivity disc specimen size is: diameter 12.7mm±0.1mm, thickness 1-2.5mm.
[0042] Example 1
[0043] Preparation of BN@PGMA@NH2-In2O3
[0044] (1) Weigh 300 g of glycidyl methacrylate, 2 g of initiator ammonium persulfate, 3 g of surfactant sodium lauryl sulfate, 800 g of deionized water, and 360 g of boron nitride, place them in a reaction vessel, react at 40° C. for 8 h, filter, wash, and dry at 50° C. for 5 h to obtain BN@PGMA;
[0045] (2) Weigh 400 g of ammonia water, 360 g of indium nitrate, and 1.0 kg of deionized water, place in a reaction vessel, react at 60° C. for 10 h, filter, wash, and dry at 40° C. for 8 h to obtain solid A;
[0046] (3) Solid A was placed in a muffle furnace, calcined at 670°C for 8 h, and passed through a 500-mesh sieve to obtain In2O3;
[0047] (4) Weigh 300 g In2O3, 400 g hydrogen peroxide, and 800 g deionized water, place in a reaction vessel, react at room temperature for 8 h, filter, wash, and dry at 50°C for 8 h to obtain OH-In2O3;
[0048] (5) Weigh 300 g of OH-In2O3, 280 g of γ-aminopropylmethyldiethoxysilane, and 800 g of deionized water, place in a reaction vessel, react at 30°C for 8 h, filter, wash, and dry at 40°C for 10 h to obtain NH2-In2O3;
[0049] (6) Weigh 300 g NH2-In2O3, 360 g BN@PGMA, 400 g anhydrous ethanol, and 800 g deionized water, place in a reaction vessel, react at 60°C for 5 h, filter, wash, and dry at 30°C for 10 h to obtain a functional filler with a composition of BN@PGMA@NH2-In2O3, recorded as M1.
[0050] Preparation of Thermoplastic Resin Composite Materials
[0051] (1) Weigh 85 parts of PP, 8 parts of functional filler M1, and 0.1 parts of Irganox 1010 according to weight, mix and stir evenly to obtain a mixture;
[0052] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PP composite material, which is recorded as P1.
[0053] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0054] Comparative Example 1
[0055] This comparative example adopts the same implementation as Example 1, except that 8 parts of the functional filler are replaced by 4 parts of boron nitride, 2 parts of In2O3 calcined in Example 1, and 2 parts of poly(glycidyl methacrylate). The other steps are the same as Example 1, and the specific steps are as follows:
[0056] (1) 85 parts of PP, 4 parts of boron nitride, 2 parts of In2O3 calcined in Example 1, 2 parts of poly(glycidyl methacrylate), and 0.1 parts of Irganox1010 were weighed and mixed and stirred to obtain a mixture;
[0057] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PP composite material, which is recorded as D1.
[0058] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0059] Comparative Example 2
[0060] This comparative example adopts the same implementation as Example 1, except that no functional filler is added. The other steps are the same as Example 1, and the specific steps are as follows:
[0061] (1) Weigh 85 parts of PP and 0.1 parts of Irganox 1010 according to weight, mix and stir evenly to obtain a mixture;
[0062] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PP composite material, which is recorded as D2.
[0063] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0064] The PP composite materials prepared in Example 1 and Comparative Examples 1-2 were made into test strips using an injection molding machine. The test results are shown in the following table:
[0065]
[0066]
[0067] It can be seen from the test results in the above table that the mechanical properties and thermal conductivity of Example 1 are better than those of Comparative Examples 1 and 2.
[0068] Example 2
[0069] Preparation of BN@PGMA@NH2-In2O3
[0070] (1) Weigh 400 g of glycidyl methacrylate, 4 g of initiator ammonium persulfate, 5 g of surfactant sodium lauryl sulfate, 1.0 kg of deionized water, and 420 g of boron nitride, place them in a reaction vessel, react at 60° C. for 12 h, filter, wash, and dry at 70° C. for 7 h to obtain BN@PGMA;
[0071] (2) Weigh 500 g of ammonia water, 400 g of indium nitrate, and 1.0 kg of deionized water, place in a reaction vessel, react at 80° C. for 12 h, filter, wash, and dry at 60° C. for 10 h to obtain solid A;
[0072] (3) Solid A was placed in a muffle furnace, calcined at 710°C for 12 h, and passed through a 500-mesh sieve to obtain In2O3;
[0073] (4) Weigh 400 g In2O3, 480 g hydrogen peroxide, and 1.0 kg deionized water, place in a reaction vessel, react at room temperature for 12 h, filter, wash, and dry at 70 ° C for 12 h to obtain OH-In2O3;
[0074] (5) Weigh 400 g of OH-In2O3, 320 g of γ-aminopropylmethyldiethoxysilane, and 1.0 kg of deionized water, place in a reaction vessel, react at 50°C for 12 h, filter, wash, and dry at 60°C for 16 h to obtain NH2-In2O3;
[0075] (6) Weigh 400 g NH2-In2O3, 420 g BN@PGMA, 500 g anhydrous ethanol, and 1.2 kg deionized water, place in a reaction vessel, react at 70°C for 7 h, filter, wash, and dry at 50°C for 14 h to obtain BN@PGMA@NH2-In2O3, which is the functional filler, denoted as M2.
[0076] Preparation of Thermoplastic Resin Composite Materials
[0077] (1) 115 parts of PBT, 16 parts of functional filler M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;
[0078] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is denoted as P2.
[0079] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0080] Comparative Example 3
[0081] This comparative example adopts the same implementation as Example 2, except that 16 parts of the functional filler are replaced by 7 parts of boron nitride, 6 parts of In2O3 calcined in Example 2, and 3 parts of poly(glycidyl methacrylate). The other steps are the same as Example 1, and the specific steps are as follows:
[0082] (1) 115 parts of PBT, 7 parts of boron nitride, 6 parts of In2O3 calcined in Example 2, 3 parts of poly(glycidyl methacrylate), 0.1 parts of antioxidant Irganox1010, 0.2 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1330 were weighed and mixed and stirred to obtain a mixture;
[0083] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is recorded as D3.
[0084] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0085] Comparative Example 4
[0086] This comparative example adopts the same implementation as Example 2, except that no functional filler is added. The other steps are the same as Example 2, and the specific steps are as follows:
[0087] (1) 115 parts of PBT, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;
[0088] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is recorded as D4.
[0089] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0090] The PBT composite materials prepared in Example 2 and Comparative Examples 3-4 were made into test strips using an injection molding machine. The test results are shown in the following table:
[0091]
[0092]
[0093] It can be seen from the test results in the above table that the mechanical properties and thermal conductivity of Example 2 are better than those of Comparative Examples 3 and 4.
[0094] Example 3
[0095] Preparation of BN@PGMA@NH2-In2O3
[0096] (1) Weigh 350 g of glycidyl methacrylate, 3 g of initiator ammonium persulfate, 4 g of surfactant sodium lauryl sulfate, 900 g of deionized water, and 390 g of boron nitride, place them in a reaction vessel, react at 50° C. for 10 h, filter, wash, and dry at 60° C. for 6 h to obtain BN@PGMA;
[0097] (2) 450 g of aqueous ammonia, 380 g of indium nitrate, and 1.1 kg of deionized water were weighed and placed in a reaction vessel. The mixture was reacted at 70° C. for 11 h. The mixture was filtered, washed, and dried at 50° C. for 9 h to obtain solid A.
[0098] (3) Solid A was placed in a muffle furnace, calcined at 690°C for 10 h, and passed through a 500-mesh sieve to obtain In2O3;
[0099] (4) Weigh 350 g In2O3, 440 g hydrogen peroxide, and 900 g deionized water, place in a reaction vessel, react at room temperature for 10 h, filter, wash, and dry at 60°C for 10 h to obtain OH-In2O3;
[0100] (5) Weigh 350 g of OH-In2O3, 300 g of γ-aminopropylmethyldiethoxysilane, and 900 g of deionized water, place in a reaction vessel, react at 40°C for 10 h, filter, wash, and dry at 50°C for 13 h to obtain NH2-In2O3;
[0101] (6) Weigh 350 g NH2-In2O3, 390 g BN@PGMA, 450 g anhydrous ethanol, and 1.0 kg deionized water, place in a reaction vessel, react at 65 °C for 6 h, filter, wash, and dry at 40 °C for 12 h to obtain BN@PGMA@NH2-In2O3, which is the functional filler, denoted as M3.
[0102] Preparation of Thermoplastic Resin Composite Materials
[0103] (1) Weigh 100 parts of PE, 12 parts of functional filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010 according to weight, mix and stir evenly to obtain a mixture;
[0104] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is denoted as P3.
[0105] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0106] Comparative Example 5
[0107] This comparative example adopts the same implementation as Example 3, except that 12 parts of the functional filler are replaced by 5 parts of boron nitride, 4 parts of In2O3 calcined in Example 3, and 3 parts of poly(glycidyl methacrylate). The other steps are the same as Example 3, and the specific steps are as follows:
[0108] (1) Weigh 100 parts by weight of PE, 5 parts of boron nitride, 4 parts of In2O3 calcined in Example 3, 3 parts of poly(glycidyl methacrylate), 0.1 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1010, mix and stir to obtain a mixture;
[0109] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is recorded as D5.
[0110] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0111] Comparative Example 6
[0112] This comparative example adopts the same implementation as Example 3, except that no functional filler is added. The other steps are the same as Example 3, and the specific steps are as follows:
[0113] (1) Weigh 100 parts of PE, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010 according to weight, mix and stir evenly to obtain a mixture;
[0114] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is recorded as D6.
[0115] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0116] The PE composite materials obtained in Example 3 and Comparative Examples 5-6 were made into test strips using an injection molding machine. The test results are shown in the following table:
[0117] Test items Test Standards unit P3 D5 D6 Tensile Strength ASTM D638 MPa 15.1 13.5 11.2 Flexural modulus ASTM D790 MPa 1290 1140 980 Izod impact strength ASTM D256 kJ / m2 3.1 2.1 1.8 Thermal conductivity ASTM D5470 W / m·K 0.63 0.61 0.42
[0118] It can be seen from the test results in the above table that the mechanical properties and thermal conductivity of Example 3 are better than those of Comparative Examples 5 and 6.
[0119] Example 4
[0120] Preparation of BN@PGMA@NH2-In2O3
[0121] (1) Weigh 335 g of glycidyl methacrylate, 2.5 g of initiator ammonium persulfate, 4.5 g of surfactant sodium lauryl sulfate, 955 g of deionized water, and 385 g of boron nitride, place them in a reaction vessel, react at 45 ° C for 11 h, filter, wash, and dry at 65 ° C for 5 h to obtain BN@PGMA;
[0122] (2) Weigh 445 g of ammonia water, 385 g of indium nitrate, and 1.05 kg of deionized water, place in a reaction vessel, react at 75° C. for 11 h, filter, wash, and dry at 40-60° C. for 8-10 h to obtain solid A;
[0123] (3) Solid A was placed in a muffle furnace, calcined at 685°C for 11 h, and passed through a 500-mesh sieve to obtain In2O3;
[0124] (4) Weigh 335 g of In2O3, 445 g of hydrogen peroxide, and 955 g of deionized water, place in a reaction vessel, react at room temperature for 11 h, filter, wash, and dry at 65 °C for 11 h to obtain OH-In2O3;
[0125] (5) Weigh 335 g of OH-In2O3, 395 g of γ-aminopropylmethyldiethoxysilane, and 465 g of deionized water, place in a reaction vessel, react at 45°C for 10 h, filter, wash, and dry at 55°C for 15 h to obtain NH2-In2O3;
[0126] (6) Weigh 365 g NH2-In2O3, 395 g BN@PGMA, 485 g anhydrous ethanol, and 1.15 kg deionized water, place in a reaction vessel, react at 68 °C for 7 h, filter, wash, and dry at 45 °C for 13 h to obtain BN@PGMA@NH2-In2O3, which is the functional filler and is recorded as M4.
[0127] Preparation of Thermoplastic Resin Composite Materials
[0128] (1) Weigh 85 parts of PA6, 14 parts of functional filler M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0129] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is denoted as P4.
[0130] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0131] Comparative Example 7
[0132] This comparative example adopts the same implementation as Example 4, except that 14 parts of the functional filler are replaced by 7 parts of boron nitride, 5 parts of In2O3 calcined in Example 4, and 2 parts of poly(glycidyl methacrylate). The other steps are the same as Example 4, and the specific steps are as follows:
[0133] (1) 85 parts of PA6, 7 parts of boron nitride, 5 parts of In2O3 calcined in Example 4, 2 parts of poly(glycidyl methacrylate), 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox1330 were weighed and mixed and stirred to obtain a mixture;
[0134] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is recorded as D7.
[0135] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0136] Comparative Example 8
[0137] This comparative example adopts the same implementation as Example 4, except that no functional filler is added. The other steps are the same as Example 4, and the specific steps are as follows:
[0138] (1) Weigh 85 parts of PA6, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0139] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material, which is recorded as D8.
[0140] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0141] The PA6 composite materials prepared in Example 4 and Comparative Examples 7-8 were made into test strips using an injection molding machine. The test results are shown in the following table:
[0142] Test items Test Standards unit P4 D7 D8 Tensile Strength ASTM D638 MPa 75.4 72.6 68.5 Flexural modulus ASTM D790 MPa 3110 2920 2700 Izod impact strength ASTM D256 kJ / m2 5.9 5.1 4.3 Thermal conductivity ASTM D5470 W / m·K 0.52 0.51 0.33
[0143] It can be seen from the test results in the above table that the mechanical properties and thermal conductivity of Example 4 are better than those of Comparative Examples 7 and 8.
[0144] Example 5
[0145] Preparation of BN@PGMA@NH2-In2O3
[0146] (1) Weigh 385 g of glycidyl methacrylate, 3.8 g of initiator ammonium persulfate, 4.9 g of surfactant sodium lauryl sulfate, 895 g of deionized water, and 415 g of boron nitride, place them in a reaction vessel, react at 58 ° C for 9 h, filter, wash, and dry at 65 ° C for 6 h to obtain BN@PGMA;
[0147] (2) Weigh 495 g of ammonia water, 385 g of indium nitrate, and 1.05 kg of deionized water, place in a reaction vessel, react at 75° C. for 11 h, filter, wash, and dry at 45° C. for 9 h to obtain solid A;
[0148] (3) Solid A was placed in a muffle furnace, calcined at 705°C for 11 h, and passed through a 500-mesh sieve to obtain In2O3;
[0149] (4) Weigh 365 g of In2O3, 475 g of hydrogen peroxide, and 955 g of deionized water, place in a reaction vessel, react at room temperature for 11 h, filter, wash, and dry at 65 °C for 11 h to obtain OH-In2O3;
[0150] (5) Weigh 375 g of OH-In2O3, 415 g of γ-aminopropylmethyldiethoxysilane, and 495 g of deionized water, place in a reaction vessel, react at 45°C for 11 h, filter, wash, and dry at 55°C for 15 h to obtain NH2-In2O3;
[0151] (6) Weigh 395 g NH2-In2O3, 415 g BN@PGMA, 495 g anhydrous ethanol, and 1.15 kg deionized water, place in a reaction vessel, react at 65 °C for 7 h, filter, wash, and dry at 45 °C for 14 h to obtain BN@PGMA@NH2-In2O3, which is the functional filler and is denoted as M5.
[0152] Preparation of Thermoplastic Resin Composite Materials
[0153] (1) Weigh 95 parts of PET, 15 parts of functional filler M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;
[0154] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is denoted as P5.
[0155] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.
[0156] Comparative Example 9
[0157] This comparative example adopts the same implementation as Example 5, except that 15 parts of the functional filler are replaced by 7 parts of boron nitride, 7 parts of In2O3 calcined in Example 5, and 1 part of poly(glycidyl methacrylate). The other steps are the same as Example 5, and the specific steps are as follows:
[0158] (1) Weigh 95 parts of PET, 7 parts of boron nitride, 7 parts of In2O3 calcined in Example 5, 1 part of poly(glycidyl methacrylate), 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant Irganox168, mix and stir to obtain a mixture;
[0159] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is recorded as D9.
[0160] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.
[0161] Comparative Example 10
[0162] This comparative example adopts the same implementation as Example 5, except that no functional filler is added. The other steps are the same as Example 5, and the specific steps are as follows:
[0163] (1) Weigh 95 parts of PET, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;
[0164] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is recorded as D10.
[0165] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.
[0166] The PET composite materials prepared in Example 5 and Comparative Examples 9-10 were made into test strips using an injection molding machine. The test results are shown in the following table:
[0167] Test items Test Standards unit P5 D9 D10 Tensile Strength ASTM D638 MPa 64.1 62.1 60.4 Flexural modulus ASTM D790 MPa 3150 2910 2780 Izod impact strength ASTM D256 kJ / m2 4.7 4.1 3.2 Thermal conductivity ASTM D5470 W / m·K 0.40 0.39 0.21
[0168] It can be seen from the test results in the above table that the mechanical properties and thermal conductivity of Example 5 are better than those of Comparative Examples 9 and 10.
[0169] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0170] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a functional filler, characterized in that: The following steps are involved: Get In2O3; Take the In2O3, hydrogen peroxide and deionized water, react at room temperature for 8-12 hours to obtain OH-In2O3; The OH-In2O3, γ-aminopropylmethyldiethoxysilane and deionized water are mixed and reacted at 30-50° C. for 8-12 hours to obtain NH2-In2O3; Glycidyl methacrylate, initiator, surfactant, deionized water and boron nitride were reacted at 40-60°C for 8-12h to obtain BN@PGMA; The NH2-In2O3, BN@PGMA, anhydrous ethanol and deionized water are mixed and reacted at 60-70°C for 5-7h to obtain a functional filler with a composition of BN@PGMA@NH2-In2O3.
2. The method for preparing the functional filler according to claim 1, characterized in that: Preparation of In2O3 The following steps are involved: Take ammonia water, indium nitrate and deionized water, react at 60-80°C for 10-12h to obtain solid A; The solid A is calcined at 670-710° C. for 8-12 hours to obtain In2O3.
3. The method for preparing the functional filler according to claim 2, characterized in that: In the step of obtaining solid A, the mass ratio of ammonia water, indium nitrate and deionized water is (40-50):(36-40):(100-120).
4. The method for preparing the functional filler according to claim 1, characterized in that: In the step of obtaining OH-In2O3, the mass ratio of In2O3, hydrogen peroxide and deionized water is (30-40): (40-48): (80-100).
5. The method for preparing the functional filler according to claim 1, characterized in that: In the step of obtaining NH2-In2O3, the mass ratio of OH-In2O3, γ-aminopropylmethyldiethoxysilane and deionized water is (30-40): (28-32): (80-100).
6. The method for preparing the functional filler according to claim 1, characterized in that: In the step of obtaining BN@PGMA, the mass ratio of glycidyl methacrylate, initiator, surfactant, deionized water and boron nitride is (30-40): (0.2-0.4): (0.3-0.5): (80-100): (36-42).
7. The method for preparing the functional filler according to claim 1 or 6, characterized in that: The initiator is ammonium persulfate; the surfactant is sodium lauryl sulfate.
8. The method for preparing the functional filler according to claim 1, characterized in that: In the step of preparing BN@PGMA@NH2-In2O3 functional filler, the mass ratio of NH2-In2O3, BN@PGMA, anhydrous ethanol and deionized water is (30-40): (36-42): (40-50): (80-120).
9. A thermoplastic resin composite material, characterized in that: It is prepared by 85-115 parts of thermoplastic resin, 8-16 parts of functional filler and 0.1-0.5 parts of antioxidant according to weight parts, and the functional filler is prepared by the preparation method according to any one of claims 1 to 8; Preferably, the antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1330; Preferably, the thermoplastic resin is selected from one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
10. A method for preparing a thermoplastic resin composite material according to claim 9, characterized in that: The following steps are involved: Weigh 85-115 parts of thermoplastic resin, 8-16 parts of functional filler and 0.1-0.5 parts of antioxidant according to weight ratio, mix and stir evenly to obtain a mixture; The mixed material is extruded and granulated to obtain a thermoplastic resin composite material.
Citation Information
Patent Citations
Epoxy resin thermal conductive composite material, preparation thereof and application
CN107189348A
Flame-retardant filler of thermoplastic resin as well as preparation method and application of flame-retardant filler
CN116444857A
Modified CeO2 filler, high-performance thermoplastic plastic containing same and preparation method of high-performance thermoplastic plastic
CN116554709A